Evaluating the Effectiveness of Technology-Based Learning through an Evidence-Based Education Framework - Arimbi Pamungkas; Rahayu Soraya; Ahmad Tohir (PT. Anagata Sembagi Education, 2026)
The accelerated adoption of technology-based learning in the post-pandemic era has encouraged educational institutions to integrate various digital innovations into instructional practices. However, increased technology use does not consistently translate into measurable learning gains, highlighting the need for evidence-based evaluation. This study aims to evaluate the effectiveness of technology-based learning through an evidence-based education framework using a Systematic Literature Review (SLR) approach. Literature searches were conducted in reputable academic databases with inclusion criteria emphasizing empirical quality and pedagogical relevance. A total of 32 empirical studies were selected and analyzed through thematic and comparative synthesis. The findings indicate that technology-based learning tends to produce positive learning outcomes when supported by evidence-informed instructional design, alignment between learning objectives, activities, and assessment, and the use of objective learning outcome measures. In contrast, technology implementations that merely substitute traditional methods without strong pedagogical grounding yield limited effects. This study concludes that the effectiveness of technology-based learning is conditional rather than universal and must be evaluated within an evidence-based education framework. The findings underscore the need to shift from innovation-driven technology adoption toward pedagogical decision-making grounded in robust empirical evidence.